Linearization of Median Genomes Under the Double-Cut-and-Join-Indel Model. (June 2019) - Avdeyev, Pavel; Jiang, Shuai; Alekseyev, Max A
Reconstruction of the median genome consisting of linear chromosomes from three given genomes is known to be intractable. There exist efficient methods for solving a relaxed version of this problem, where the median genome is allowed to have circular chromosomes. We propose a method for construction of an approximate solution to the original problem from a solution to the relaxed problem and prove a bound on its approximation error. Our method also provides insights into the combinatorial structure of genome transformations with respect to appearance of circular chromosomes.